2000
DOI: 10.4049/jimmunol.165.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Differential Expression of Chemokines in Th1 and Th2 Cells Is Dependent on Stat6 But Not Stat4

Abstract: The in vivo function of Th cell subsets is largely dependent on the ability of differentiated CD4+ T cells to be recruited to specific sites and secrete restricted sets of cytokines. In this paper we demonstrate that Th1 and Th2 cells secrete discrete patterns of chemokines, small m.w. cytokines that function as chemoattractants in inflammatory reactions. Th2 cells secrete macrophage-derived chemokine and T cell activation gene 3, and acquisition of this pattern of expression is dependent on Stat6. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…To verify that the BM compartment was reconstituted with donor BM, splenocytes were stimulated with anti-CD3, and the supernatants were assayed for IL-4 production by ELISA. Previous work has demonstrated that STAT6 Ϫ/Ϫ lymphocytes secrete significantly less IL-4 than wt lymphocytes when stimulated with anti-CD3 (19,31). Both STAT6 Ϫ/Ϫ BM3 STAT6 Ϫ/Ϫ mice and STAT6 Ϫ/Ϫ BM3wt mice made significantly less IL-4 than wt BM3wt mice, demonstrating that the BM grafts were successful (Fig.…”
Section: Peptide-specific T Cells From Bm Chimeras Fail To Reject 4t1mentioning
confidence: 67%
“…To verify that the BM compartment was reconstituted with donor BM, splenocytes were stimulated with anti-CD3, and the supernatants were assayed for IL-4 production by ELISA. Previous work has demonstrated that STAT6 Ϫ/Ϫ lymphocytes secrete significantly less IL-4 than wt lymphocytes when stimulated with anti-CD3 (19,31). Both STAT6 Ϫ/Ϫ BM3 STAT6 Ϫ/Ϫ mice and STAT6 Ϫ/Ϫ BM3wt mice made significantly less IL-4 than wt BM3wt mice, demonstrating that the BM grafts were successful (Fig.…”
Section: Peptide-specific T Cells From Bm Chimeras Fail To Reject 4t1mentioning
confidence: 67%
“…T he chemokines thymus-and activation-regulated chemokine/CC chemokine ligand 17 (CCL17) 3 and macrophage-derived chemokine (MDC/CCL22) can be classified as both homeostatic and inflammatory chemokines and exert their effects via the chemokine receptor CCR4. CCR4 is expressed on Th2 cells (1)(2)(3)(4), CLA ϩ cutaneous memory T cells (5), NK cells (6), thymocytes (7,8), immature dendritic cells, basophils, and platelets (9,10).…”
mentioning
confidence: 99%
“…CCR4 is expressed on Th2 cells (1)(2)(3)(4), CLA ϩ cutaneous memory T cells (5), NK cells (6), thymocytes (7,8), immature dendritic cells, basophils, and platelets (9,10). Due to the fact that CCR4 was initially thought to be exclusively expressed on Th2 cells, early pathological roles for CCR4 concentrated on known Th2-mediated conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the source of XCL1 within the immune system is still poorly defined. On the one hand, lymphotactin synthesis was originally described as strictly confined to CD8 ϩ T cells (8 -12); more recently, XCL1 expression was also reported in several other leukocyte populations, including NK cells (7,13,14), dendritic cells (15), activated mast cells (16), TCR ␥␦ ϩ T cells (17,18), and even CD4 ϩ T cells (19), especially those belonging to the Th1 subset (20,21). In most cases, however, no quantitative comparisons between different cell populations were performed, and the ability to produce XCL1 was mostly evaluated by nonquantitative PCR approaches.…”
mentioning
confidence: 99%